A story-telling cloth approach to motivating cervical cancer screening in Mali - Crippin, Tiffani; Tounkara, Karamoko; Squibb, Eliza; Beseme, Sarah; Barry, Katherine; Sangare, Kotou; Coulibaly, Saidou; Fané, Pinda; Bagayoko, Aliou; Koita, Ousmane A.; Teguété, Ibrahima; De Groot, Anne S. (Frontiers in Public Health, 2022)
Ninety percent of deaths from Cervical cancer (CC) caused by Human Papilloma Virus (HPV) occur in low- and middle-income countries. CC is the 2nd most common cause of cancer in women in West Africa, where 12,000 women develop cervical cancer and more than 6,000 die from the disease, annually. While HPV vaccination and CC screening have dramatically reduced the incidence of CC and mortality from CC in developed countries, prevention of CC in West Africa is often limited to visual inspection of the cervix and surgical intervention. In previous studies of CC in Mali, we demonstrated that knowledge about the link between HPV and CC is limited, and that screening for CC is often delayed until women are symptomatic. For this intervention, a story-telling cloth (West African-style printed pagne) was designed for use as a starting point for educational sessions run by community health workers. Community outreach using the cloth during 6 months of 2015 resulted in a 5-fold higher uptake of cervical cancer screening and increased awareness of the potential to vaccinate adolescents against CC. 3,271 women were motivated to visit one of five participating clinics for CC screening, where a mere 600 women had been screened during the previous year. This study shows that a comprehensive, visual, community-centered education campaign coupled with coordinated support for local clinics improves uptake of CC screening.